Electrochemical Reduction of α-Ketoglutaric Acid Oxime - P. Babu, D.; Jayarama Reddy, S. (Asian Journal of Chemistry, 2010)
The electrochemical reduction behaviour of α-ketoglutaric acid oxime (α-KGO) has been studied at hanging mercury drop electrode (HMDE) and dropping mercury electrode (DME) in various supporting electrolytes using cyclic voltammetry, chronopotentiommetry and d.c. polarograpy. Mechanism of the reduction process was discussed and kinetic parameters evaluated and reported. The reduction product formed is shown to be glutamic acid.